RELIGIOUS PLURALITY AND THE URGENCY OF INTERCULTURAL COMMUNICATION IN INDONESIA - Muhammad Thahir (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2023)
This article elucidates the crucial significance of cross-cultural communication in the context of religious diversity. Religious diversity is an established reality that can be attributed to the genesis of each religious tradition in a multicultural milieu. Inadequate handling of the diverse array of global religions may give rise to potential issues of instability and disharmony among heterogeneous religious communities. This article examines plausible behavioral trends that may be employed to foster amity and collective unity among religious groups that possess inherent diversity. The present article utilizes Luc Reychler's indicator formula as a novel methodology for addressing issues. As mentioned earlier, the indicators encompass a diverse range of components deemed essential for promoting peaceful outcomes. The variables mentioned above include but are not limited to, efficient communication methods, a robust conflict resolution mechanism, a conducive environment for integration (also known as bridging social capital), a sufficient number of leaders who prioritize peace, and unbiased frameworks.